Extension note - Primary health care: 30 years of extension work - Florêncio da Cunha Fortes, Pedro; de Almeida, Ipojucan; Rose Sampaio Fortes, Margarete (Guará Journal, 2025)
The "Promotion of Primary Health Care in a Community" outreach program, affiliated with the Center for Health Sciences (CCS) at the Federal University of Espírito Santo (UFES), is the institution's oldest outreach initiative. In 2014, it celebrated 30 years of registration with the Office of the Vice-Rector for Outreach (ProEx). Its long-standing history demonstrates its commitment to vibrant and proactive university outreach, bringing dozens of generations of undergraduate students to experience learning processes in a region of evident social and economic vulnerability. This is where UFES outreach achieves its objectives through community engagement and citizenship development.